Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Produktivitas Kerja Karyawan Pada Perum Damri Cabang Lampung - Nabila Fuad, Lutfi; Novila, Pipit; Silvia, Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), 2024)
This research aims to determine the influence of work discipline and work environment on employee work productivity at Perum Damri Lampung branch. This research is associative with a quantitative approach using primary and secondary data. A sample of 70 respondents was taken using the random sampling method with data collection techniques using a questionnaire. The data analysis techniques used in this research are validity testing, reliability testing, multiple linear regression and hypotheses. The model was tested using SPSS version 24. The results showed that work discipline partially had a significant positive effect on employee work productivity with a value of tcount > ttable (3.984 > 1.996). The work environment partially has a significant positive effect on employee work productivity with a value of tcount > ttable (9.494 > 1.996). Work discipline and work environment simultaneously influence employee work productivity with a value of Fcount > Ftable (60.346 > 3.13). The R Square Determination Coefficient value in this research is 0.643, where work discipline and work environment variables influence employee work productivity by 64.3%, while the remaining 35.7% is influenced by other factors. Keywords: Work Discipline, Work Environment, Work Productivity.